When Agreement isn't Agreement: Deflected Agreement in Najdi Arabic as Aspect - Connor Caston Rouillier (Glossa, 2023)
In modern Arabic varieties, subject-verb agreement is complicated by plural nouns which can occur with both plural and singular verbs. These have been called strict and deflected agreement respectively. In some varieties such as Modern Standard Arabic, this deflected agreement is fixed and determined by animacy or other features; however, in other varieties such as Najdi Arabic (central Saudi Arabia), whether strict or deflected agreement occurs is less predictable. Kramer & Winchester (2017) have argued that the selection of verb form corresponds to a difference in meaning, specifically, a herd/clump as opposed to an individuated interpretation, which they locate in the nominal features of the noun. However, based on the results of two experiments, this paper argues for an alternate analysis that this meaning difference originates on the verb and corresponds to a speaker’s mental representation of the event structure. This finding leads to the conclusion that only strict agreement is actually an example of subject-verb agreement, while deflected agreement serves to mark features of the event. This usage of deflected agreement to express event structure, while initially surprising, flows from existing understandings of cognition of number and event semantics.